Organizational experience of the Civil Defense Scientific Research Center in the diagnosis of COVID-19 - Mireida Rodríguez Acosta; Marta Dubed Echevarría; María Teresa Pérez Guevara; Otto Cruz Sui; Nibaldo Luis González Sosa; Tamara Hernández Sánchez; José Ángel Columbié Gamboa; Alejandro Velázquez Pupo (Revista Cubana de Medicina Militar)
Facing the COVID-19 epidemic in Cuba has required the development of new capacities for its diagnosis in the molecular biology laboratories of different scientific and health institutions. The objective of this work is to show the experience of the Cuban Civil Defense Scientific Research Center in organizing the diagnosis of COVID-19. Guiding documents for the Center's work, its biosafety program, and those reported by the World Health Organization for dealing with the pandemic were reviewed. The experience of the structure adopted by the entity to ensure an uninterrupted diagnosis, the functions of the Steering Group and the sequence of activities carried out is exposed; highlighting the training of personnel in the management of biological risks and the prevention measures adopted. The proper use of collective and individual protection means, the safe handling of biological samples and cooperation with other entities, have allowed the fulfillment of the entrusted task, without the occurrence of accidents that compromise the health of the personnel working in the diagnosis, nor effects on the community and the environment.